2015
DOI: 10.3386/w21004
|View full text |Cite
|
Sign up to set email alerts
|

The Marriage Market, Labor Supply and Education Choice

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 0 publications
0
53
0
Order By: Relevance
“…We interpret the economic mechanism behind the heterogeneity in the e↵ect of school construction by ethnic group as evidence of the role of the marriage market in driving educational choices and hence how households respond to education reforms. While marriage outcomes are generally considered an important component of the returns to education, especially for women (Goldin, 2006;Chiappori et al, 2017), it is typically di cult to empirically observe them and to identify their actual impact. In this paper, we study the marriage market returns to education as reflected in the value of the bride price and show that they have sizable e↵ects on parents' decisions to educate daughters, particularly in response to policies that reduce the cost of schooling.…”
Section: Introductionmentioning
confidence: 99%
“…We interpret the economic mechanism behind the heterogeneity in the e↵ect of school construction by ethnic group as evidence of the role of the marriage market in driving educational choices and hence how households respond to education reforms. While marriage outcomes are generally considered an important component of the returns to education, especially for women (Goldin, 2006;Chiappori et al, 2017), it is typically di cult to empirically observe them and to identify their actual impact. In this paper, we study the marriage market returns to education as reflected in the value of the bride price and show that they have sizable e↵ects on parents' decisions to educate daughters, particularly in response to policies that reduce the cost of schooling.…”
Section: Introductionmentioning
confidence: 99%
“…53 This is both because the number of college men was lower, and due to changing tastes for partners.54 Ge(2011)predicted female college graduation would drop 8% without the marriage market return to education Chiappori, Iyigun, and. Weiss (2009), Chiappori, Costa-Dias, andMeghir (2018),Fernández andWong (2011) andLow (2014) also studied the interaction of the marriage market and education.…”
mentioning
confidence: 99%
“…The key insight of the SEV approach is that only the sharing rule over the economic part of the surplus matters for assortativeness in marriage (see Choo and Siow (2006), Chiappori et al (2017) and Chiappori et al (2018)). Specifically, it can be shown that there exists a collection of values U IJ and V IJ that add up to the economic surplus Z IJ for all possible matching combinations, and such that the individual utilities of man i and woman j married to each other in the stable equilibrium are, respectively,…”
Section: The Separable Extreme Value Index Of Assortativenessmentioning
confidence: 99%